2022
DOI: 10.1038/s41377-022-00853-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cost-effective integrated spectrometers

Abstract: The proliferation of Internet-of-Things has promoted a wide variety of emerging applications that require compact, lightweight, and low-cost optical spectrometers. While substantial progresses have been made in the miniaturization of spectrometers, most of them are with a major focus on the technical side but tend to feature a lower technology readiness level for manufacturability. More importantly, in spite of the advancement in miniaturized spectrometers, their performance and the metrics of real-life applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 108 publications
0
46
0
Order By: Relevance
“…Nevertheless, their bulky sizes and delicate systems make them ill-suited for use outside of laboratories. Driven by the ever-growing demand for instantaneous and cost-effective spectroscopic analysis, integrated spectrometers have attracted tremendous research interest . The chip-scale miniaturization of spectrometers may reshape the landscape of spectroscopy and open up new opportunities for applications that require in situ characterization or high-density integration, e.g., food safety detection, hyperspectral imaging, intelligent health monitoring, and lab-on-a-chip .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, their bulky sizes and delicate systems make them ill-suited for use outside of laboratories. Driven by the ever-growing demand for instantaneous and cost-effective spectroscopic analysis, integrated spectrometers have attracted tremendous research interest . The chip-scale miniaturization of spectrometers may reshape the landscape of spectroscopy and open up new opportunities for applications that require in situ characterization or high-density integration, e.g., food safety detection, hyperspectral imaging, intelligent health monitoring, and lab-on-a-chip .…”
Section: Introductionmentioning
confidence: 99%
“…The channelization method is discussed in the SI, Section S6. The decorrelation property of the channelized A is evaluated with singular value decomposition (SVD), which is to decompose A into the product of two singular spaces (U, V) and a diagonal matrix (∑) 46 = A U V T (5) Singular values (σ i ) are the descending diagonal elements of ∑. We calculate the σ i curves with varying N ch , as shown in Figure 4e.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Optical spectrometry is a powerful analysis tool in scientific research and in industry. Traditional laboratory spectrometer systems with strong analytic ability have bulky optical components, moving parts, and long path lengths, which cannot meet the requirement of the rapidly growing applications of mobile and portable detection [167]. Miniaturized spectrometers are very attractive in the applications where low cost, lightweight, and tailorable optoelectronic characteristics are preferred.…”
Section: Spectrometersmentioning
confidence: 99%
“…The spectrum of Cs 3d shows two peaks located at 724. 3 The device structure of the photodetector based on the printed perovskite film is illustrated in Figure 2a. Mo electrodes were first deposited by physical vapor deposition with a channel width of 20 μm and length of 30 μm on the flexible PET substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Miniaturized spectrometers with advantages of portability and low cost and power consumption have attracted much attention due to their potential in advanced application scenarios, including wearable devices, hyperspectral imaging, and internet of things. Computational spectrum reconstruction based on a series of response-modulated photodetectors with a gradient bandgap is one of the most promising methods for achieving such miniaturized spectroscopy systems. For instance, Yang et al successfully demonstrate a miniaturized spectrometer at the scale of tens of micrometers using a single compositionally graded CdS x Se 1– x nanowire . Recently, halide perovskites have also been used in photodetectors for human visual-like spectrum projection, full-color detection, and multispectral recognition owing to their outstanding properties such as facile solution-process fabrication, excellent light harvesting coefficients, and tunable bandgaps. Xu et al demonstrated a miniaturized multispectral detector based on a composition-gradient perovskite microwire detector array, offering a response edge ranging from 450 to 790 nm .…”
Section: Introductionmentioning
confidence: 99%